Correlation between immunization status and pediatric diphtheria patients outcomes in the Sampang District, 2011-2015 - Kevin Sastra Dhinata; Atika Atika; Dominicus Husada; Dwiyanti Puspitasari (Paediatrica Indonesiana, 2018)
Background The number of diphtheria cases recently increased, such that an outbreak was declared in East Java Province, which includes the Sampang District. Immunization completion status is a determining factor for diptheria infection. Objective To investigate for correlations between immunization status and outcomes (severity level, fatality, and complications) of diphtheria patients in the Sampang District. Methods This analytic, cross-sectional study used secondary data from the East Java Provincial Health Office on diphteria patients aged 0-20 years during the 2011-2015 outbreak in the Sampang District and interviews with diphtheria patients in that region. The Diphtheria Research Team of Soetomo Hospital collected data on immunization status, diphtheria severity (mild, moderate, or severe), case fatality (died or survived), and complications in the patients (with or without complications). Spearman’s, Chi-square, and Fisher’s exact tests were used for data analyses, accordingly. Results Seventy-one patients with clinical diphtheria were identified, 17 of whom were confirmed with positive culture results. The case fatality rates were 7% in patients with clinical and 5.9% in confirmed diphtheria. There were no correlations between patient immunization status and severity (P=0.469 clinical, P=0.610 confirmed), or fatality (P=0.618 clinical, P=0.294 confirmed) of diphtheria in the clinical and confirmed diphtheria patients. However, there was a correlation between patient immunization status and the emergence of complications in clinical (P=0.013), but not in confirmed (P=0.620) diphtheria patients. Conclusion There is a correlation between immunization status and complications in clinical diphtheria patients. Such a correlation is not found in confirmed diphtheria cases because none of the patients had complete immunization status.